2010
DOI: 10.1038/tpj.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism of the GTP-cyclohydrolase I feedback regulator gene alters transcriptional activity and may affect response to SSRI antidepressants

Abstract: Tetrahydrobiopterin (BH 4 ) is an essential cofactor for synthesis of many neurotransmitters including serotonin. In serotonergic neurons, BH 4 is tightly regulated by GTP-cyclohydrolase I feedback regulator (GFRP). Given the pivotal role of the serotonergic system in mood disorders and selective serotonin reuptake inhibitors (SSRIs) antidepressant function, we tested the hypothesis that GFRP gene (GCHFR) variants would modify response to antidepressants in subjects with major depression. Two single nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…We also observed association between promoter variants of the Spr gene and susceptibility to mood disorders as well as to antidepressant treatment response (McHugh et al, 2009). A similar analysis of promoter variants for another enzyme in the BH4 biosynthetic pathway, GTPcyclohydrolase I feedback regulator (GFRP), also suggested an association with antidepressant responses (McHugh et al, 2011).…”
Section: A N U S C R I P Tsupporting
confidence: 57%
“…We also observed association between promoter variants of the Spr gene and susceptibility to mood disorders as well as to antidepressant treatment response (McHugh et al, 2009). A similar analysis of promoter variants for another enzyme in the BH4 biosynthetic pathway, GTPcyclohydrolase I feedback regulator (GFRP), also suggested an association with antidepressant responses (McHugh et al, 2011).…”
Section: A N U S C R I P Tsupporting
confidence: 57%
“…n Advantages of genome-wide expression profiling Earlier attempts to identify genetic biomarkers for antidepressant drug response have focused on DNA polymorphism using either the candidate gene approach, most notably serotoninrelated genes such as the serotonin transporter SLC6A4 [7][8] and serotonin receptors or other candidate genes related to serotonin or corticotrophin signaling [11][12][13][14]. None of these genes studied by the candidate approach were among those identified in the current study.…”
Section: Discussionmentioning
confidence: 87%
“…However, the translation of these findings into clinical practice has been hampered by the problem of negative replication, and a recent meta-ana lysis of all studies on the serotonin transporter polymorphism has demonstrated that the effect is not significant [10]. Similarly, candidate gene studies on SSRI efficacy in major depression have examined other genes as predictors for SSRI response, including the HTR2A serotonin receptor [11], genes regulating the corticotropin-releasing factor system [12], the GTP-cyclohydrolase I feedback regulator gene [13] and G(a)i2 [14], However, to date the evident impact on drug response is not sufficient for using these genes as biomarkers for individual response prediction.…”
mentioning
confidence: 99%
“…Tetrahydrobiopterin pathway, depicting key regions of SPR activity, and the various techniques performed to assess this under treatment with tranilast (figure amended from ref (33)).…”
Section: Discussionmentioning
confidence: 99%